La « double » mobilité sociale d’Hélène Ramon. Réflexivité sur le genre et examen des trajectoires sociales - Joseph Cacciari (Genre, Sexualité et Société)
Can the inversion of gender relations lead to social mobility from the point of view of the respondents? This is the central question of this article. The argument is based on a contextualised approach to upward social mobility in working-class circles, that of Hélène Ramon, 38 years old, a dental technician, separated, mother of a ten-year-old daughter. This case study constitutes the main material for the reflection. It will show how Hélène Ramon’s feeling of mobility, if it can be understood on the basis of variables such as educational capital or professional position, comes to be duplicated to find its main meaning through the inversion of the order of gender positions in the respondent's kinship group.